The Role of Nurses During a National Disaster, 2013 - Nordland Research Institute (Nordland Research Institute, 2017)
This study examined the role of nurses during the events and in the aftermath of 22nd of July 2011. The study was conducted by Nordland Research Institute on behalf of NSF. Among the themes that were explored were different aspects of the work, the duration of tasks, and the nurses background. The study has contributed to insight to the professional activities in the health services, both during the emergency phase and in the aftermath of 22nd of July 2011. For further information about ”The Role of Nurses During a National Disaster, 2013”, please contact the principal investigator.